Efficiency in the Use of the Region’s Population Social Protection Potential. / Eficiencia del uso del potencial de protección social de la población en la región. - RAZINKOV, P.I; MARTYNOV, D.V; RAZINKOVA, O.P (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article discusses the directions of increasing the efficiency of using the potential of social protection of the region's population. It was revealed that the potential of social protection, in contrast to its socio-economic potential, has a limited importance, since it is formed in a planned manner, depending on the availability of financial and resources of another nature. Therefore, when analyzing the level of formation and use of the potential of social protection of the region, it is possible to assess the level of use of its structural components to improve.RESUMEN El artículo discute las direcciones para incrementar la eficiencia del uso del potencial de protección social de la población en la región. Se reveló que dicho potencial, en contraste con su potencial socio-económico, tiene una importancia limitada, ya que se forma de manera planificada, dependiendo de la disponibilidad de recursos financieros y de cualquier otra naturaleza. Por tanto, al analizar el aprovechamiento del potencial de protección social de la región, es posible evaluar el nivel de aprovechamiento de sus componentes estructurales para mejorar.